Feminism (2019) by Deborah Cameron (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2022)
Feminism is a small compilation of the debates that have run through the movement, especially in the West. Narrated in a simple and entertaining style, based on compilations of different themes, studies and references, it addresses the main questions of feminism and exposes the answers that have been provided from different positions.TECHNICAL SHEET OF THE BOOKTitle: Feminism. Author: Cameron, Deborah. Translation: Tercero, Maria Enguix. Publisher: Alianza Editorial. Language: Spanish. Pages: 176. Year: 2019. Place: Madrid. EBOOK ISBN: 978-84-9181-541-9. Original title: Feminism. 1st edition in English, 2018, Great Britain. Profile Books LTD.